2008
DOI: 10.1016/j.immuni.2008.04.021
|View full text |Cite
|
Sign up to set email alerts
|

The TNF-Family Receptor DR3 is Essential for Diverse T Cell-Mediated Inflammatory Diseases

Abstract: DR3 (TRAMP, LARD, WSL-1, TNFRSF25) is a death-domain-containing tumor necrosis factor (TNF)-family receptor primarily expressed on T cells. TL1A, the TNF-family ligand for DR3, can costimulate T cells, but the physiological function of TL1A-DR3 interactions in immune responses is not known. Using DR3-deficient mice, we identified DR3 as the receptor responsible for TL1A-induced T cell costimulation and dendritic cells as the likely source for TL1A during T cell activation. Despite its role in costimulation, DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
283
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 198 publications
(316 citation statements)
references
References 33 publications
25
283
2
6
Order By: Relevance
“…Consistent with these findings transgenic mice that constitutively express TL1A have increased levels of IL-13 and IL-17 but not IFN-g under steady-state conditions [15,16]. However, other studies have shown that addition of TL1A or agonist anti-DR3 mAb enhances the production of both IL-4 and IFN-g during in vitro activation of naïve CD4 1 T cells [5,14]. To decipher the role of DR3 in host immunity to infection, we have examined the immune response against Salmonella enterica serovar Typhimurium in DR3-deficient mice.…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…Consistent with these findings transgenic mice that constitutively express TL1A have increased levels of IL-13 and IL-17 but not IFN-g under steady-state conditions [15,16]. However, other studies have shown that addition of TL1A or agonist anti-DR3 mAb enhances the production of both IL-4 and IFN-g during in vitro activation of naïve CD4 1 T cells [5,14]. To decipher the role of DR3 in host immunity to infection, we have examined the immune response against Salmonella enterica serovar Typhimurium in DR3-deficient mice.…”
Section: Introductionsupporting
confidence: 60%
“…Infection with S. enterica Typhimurium induces expression of TL1A in macrophages TL1A expression is transiently increased in macrophages and dendritic cells by diverse stimuli, including LPS and immune complexes [5,12]. To determine whether TL1A is upregulated during infection, mice were challenged with S. enterica Typhimurium and TL1A mRNA expression measured in the spleen by quantitative RT-PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations